"Két Ukrajna”? : Ukrajna megosztottságának történeti gyökerei - Varga, Beáta (Közép-Európai Közlemények, 2017)
Ukraine’s division today is mostly a consequence of its peripheral status: throughout the course of history the Ukrainians should (have) achieve(d) independence and the establishment of a sovereign state in the political vacuum that developed due to the rivalry of the neighboring great powers. In the East-European region Ukraine did have a state several times for a short period and in a much debated way, but it only gained complete sovereignity in 1991, while Russia had considered Ukraine, which „voluntarily joined” the empire in 1654, part of the Russian state. What has also contributed to Ukraine’s division and the belated establishment of a state was that it did not have a unified national identity: in East- and Central Ukraine, which were continuously under Russian rule from the middle of the 17th century, a strong national movement could never develop. Then, following the partition of Poland, when West-Ukraine – with the exception of Galicia – became part of Russia, most of the Ukrainian territories belonged to – but did not comprise – one state. In Galicia, which was the western border of the eastern Slavic territories and was under the considerably liberal rule of Austria, and was called „the Ukrainian Piedmont”, a stronger national self-consciousness developed after 1772. That is why it was there that the idea of a unified Ukrainian state was conceived first, the realization of which, however, took more than a hundred years, because of the division and weak national consciousness of the Ukrainians.